2013
DOI: 10.1080/19361610.2013.825750
|View full text |Cite
|
Sign up to set email alerts
|

What People Think About Torture: Torture Is Inherently Bad … Unless It Can Save Someone I Love

Abstract: Prior research suggests people's abstract views of torture are often negative. We suspected, however, that those views might not fully represent torture perceptions in a scenario where they felt closeness to the potential victims. To test this idea, participants read a scenario about a crisis situation and completed measurements of their support for torture usage in the scenario. Scenarios varied in their degree of personal closeness to the victim. Results from 2 studies suggest that people were considerably m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…Consistent with the previously discussed findings from Houck and Conway (2013), a synthesis of polls between 2001 and 2009 revealed that self-reported attitudes to broadly framed questions about torture were largely negative; most opposed torture (Gronke et al, 2010). Although there is variability, most polling data from the United States and abroad suggests that while people tend to oppose torture at a very broad level, they often support it given a particular set of circumstances (for discussion, see Houck & Conway, 2013). For example, a 2012 poll supports the idea that people are generally opposed to torture by revealing that 66% of Americans said they do not think the government should use torture against suspected terrorists (Canseco, 2012).…”
Section: Common Torture Attitudessupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the previously discussed findings from Houck and Conway (2013), a synthesis of polls between 2001 and 2009 revealed that self-reported attitudes to broadly framed questions about torture were largely negative; most opposed torture (Gronke et al, 2010). Although there is variability, most polling data from the United States and abroad suggests that while people tend to oppose torture at a very broad level, they often support it given a particular set of circumstances (for discussion, see Houck & Conway, 2013). For example, a 2012 poll supports the idea that people are generally opposed to torture by revealing that 66% of Americans said they do not think the government should use torture against suspected terrorists (Canseco, 2012).…”
Section: Common Torture Attitudessupporting
confidence: 93%
“…Peer-reviewed research. Although peerreviewed research pertaining to torture attitudes is quite limited, the research that does exist indicates that people hold discrepant views of torture (Houck & Conway, 2013). On the one hand, there is a significant amount of evidence suggesting that people are inherently averse to harming others, even in cases where harmful actions against one person would save many lives (e.g., Greene, Sommerville, Nystrom, Darley, & Cohen, 2001;Mendez et al, 2005;Mikhail, 2000).…”
Section: Common Torture Attitudesmentioning
confidence: 99%
“…This is an important finding because it moves the conversation on civil liberties towards a greater consideration of social identity theory (Tajfel & Turner, 1979) -that the group we identify with is salient and important to considerations of liberty. While prior research showed that individuals are more willing to support torture and are more likely to believe that the torture will be effective when it is to save ingroup members (Houck & Conway, 2013;Houck et al, 2014), this study showed that the effect of threat was largest when considering the removal of others' rights, not our own, lending preliminary support for a punitive model of restrictions. This suggests that in order to support civil liberties, we need to either cognitively expand the ingroup -so fewer individuals are left in the outgroup position -or suggest alternative punitive measures in lieu of restricting civil liberties.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, the support for torture increases as a function of psychological distance. For example, being personally close to a victim (e.g., a loved one) who can be saved by torturing a perpetrator increased support of torture of the perpetrator (Houck & Conway, 2013) and increased estimates of the effectiveness of such torture (Houck, Conway, & Repke, 2014).…”
Section: Why Do Laypersons Policymakers and Interrogators Beliementioning
confidence: 99%